Sustainable use of sewage sludge as a casing material for button mushroom (Agaricus bisporus) cultivation: experimental and prediction modeling studies for uptake of metal elements (2022)
The present study focused on the use of sewage sludge (SS) as a casing material amendment and the potential uptake of metal elements by the cultivated white button (Agaricus bisporus: MS-39) mushroom. Laboratory experiments were performed under controlled environmental conditions to grow A. bisporus on the composted wheat straw substrate for 50 days. Different treatments (0, 50, 100, 150, and 200 g/kg) of casing material were prepared by mixing garden and dried SS and applied on the mushroom substrate after proper sterilization. The results revealed that SS application was significant (p < 0.05) in accelerating mushroom yield with a biological efficiency of 65.02% for the mixing rate of 200 g/kg. Moreover, the maximum bioaccumulation of selected metal elements (Cu, Cr, Cd, Fe, Mn, and Zn) was observed using the same treatment. Additionally, the multiple regression models constructed for the uptake prediction of metal elements showed an acceptable coefficient of determination (R2 > 0.9900), high model efficiency (ME > 0.98), and low root mean square error (RMSE < 0.410) values, respectively. The findings of this study represent sustainable use of SS for the formulation of mushroom casing material contributing toward synergistic agro-economy generation and waste management.